Researching a segmented market: reflections on telephone interviewing. Issue 7 (18th July 2016) - Lord, Rhiannon; Bolton, Nicola; Fleming, Scott; Anderson, Melissa
Abstract : Purpose: The purpose of this paper was to review the effectiveness of telephone interviewing for capturing data and to consider in particular the challenges faced by telephone interviewers when capturing information about market segments. Design/methodology/approach: The platform for this methodological critique was a market segment analysis commissioned by Sport Wales which involved a series of 85 telephone interviews completed during 2010. Two focus groups involving the six interviewers involved in the study were convened to reflect on the researchers' experiences and the implications for business and management research. Findings: There are three principal sets of findings. First, although telephone interviewing is generally a cost-effective data collection method, it is important to consider both the actual costs (i.e. time spent planning and conducting interviews) as well as the opportunity costs (i.e. missed appointments, "chasing participants"). Second, researchers need to be sensitised to and sensitive to the demographic characteristics of telephone interviewees (insofar as these are knowable) because responses are influenced by them. Third, the anonymity of telephone interviews may be more conducive for discussing sensitive issues than face-to-face interactions. Originality/value: The present study adds to this modest body of literature on the implementation of telephone interviewing as a research technique of business and management. It provides valuable methodological background detail about the intricate, personal experiences of researchers undertaking this method "at a distance" and without visual cues, and makes explicit the challenges of telephone interviewing for the purposes of data capture.